Improvement of high temperature polymer electrolyte fuel cell performance with phosphoric acid-doped polybenzimidazole ionomer binder in catalyst layer - Kim, Jeong-Hi; Kim, Hyoung-Juhn; Lim, Tae-Hoon; Lee, Ho-In (ELSEVIER SCIENCE INC, 2007)
Pt/C catalyst layers with a phosphoric acid-doped polybenzimidazole ionomer binder were used as the electrode for a high temperature polymer electrolyte fuel cell. Catalyst layers were prepared with a transparent ionomer solution in trifluoroacetic acid solvent, an opaque ionomer dispersion in a trifluoroacetic acid/propanol-based solvent, and a mixture of the above two substances. The nano-sized ionomers in the transparent ionomer solution were located inside the primary pores, while the micro-sized ionomer agglomerates in the opaque ionomer dispersion were located outside the primary pores and produced proper proton conduction connections without blocking the primary pore openings. The optimum cell performance was obtained with an appropriate mixture of the transparent ionomer solution and opaque ionomer dispersion.
Keywords: POLY(2,5-BENZIMIDAZOLE) ABPBI; MEMBRANES; METHANOL; CONDUCTIVITY; CARBON; WATER